PERBANDINGAN KEJADIAN PNEUMONIA PADA BALITA YANG TINGGAL DI DATARAN TINGGI DAN DATARAN RENDAH DITINJAU DARI FAKTOR IKLIM KOTA SEMARANG TAHUN 2012 – 2016 - Tri Amdani Kumbasari; Budiyono Budiyono; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Climate factors may influence of pneumonia. The temperature and humidity in Semarang had increased 0,3⁰C and 1% during 2011-2015 respectively. The trendline of pneumonia showed that incident of pneumonia in under-five children had increased from 2.719 to 5.349 cases during 2013-2015. This study aimed to analyze the differences of pneumonia in under-five children who live in highland and lowland in term of climate factors in Semarang City in 2012-2016. Incidence data of under-five children pneumonia was obtained from recapitulation monthly report at primary health care of Bandarharjo and Mijen. Data of temperature, humidity, and rainfall was obtained from data monthly report from Agency for Meteorology, Climatology and Geophysics (BMKG) Semarang City. Subject consisted of patients visited primary health care of Bandarharjo and Mijen from 2012 to 2016. The sample of this research is using total sampling. The research used observational research with cross sectional descriptive design. Statistic analytic was used Mann Whitney and independent T-test with α=5%. The results showed average incidence of pneumonia in Bandarharjo were 32 cases while in Mijen 28 cases, respectively temperature, humidity and rainfall were 28,2⁰C, 76,5% and 176,1 mm/month while in Mijen 26,4⁰C, 76,2% and 338,9 mm/month. There is no difference in the incidence of pneumonia in under-five children (p=0,102) and humidity (p=0,585) in highland and lowland. There were significantly difference of temperature and rainfall in highland and lowland (p<0,01). There were significantly difference in the incidence of pneumonia in under-five children in term of humidity (p<0,01). There were no significantly difference in the incidence of pneumonia in under-five children in term of temperature (p=572) and rainfall (p=0,809). The research conclusion that humidity was potential risk factor for pneumonia in under-five children in Semarang City.